Fabrication of a nanostructured TiO2/carbon nanotube composite electrode for voltammetric and impedimetric determination of NTO explosive in the water and soil samples. Issue 11 (1st September 2016) - Damiri, Sajjad; Pouretedal, Hamid Reza; Heidari, Amin
ABSTRACT: An electrochemical oxidation route was developed for sensitive and selective assay of nitrotriazolone (NTO) explosive in some environmental samples on a multi-walled carbon nanotube (MWCNTs)/TiO2 nanocomposite paste electrode, for prevention of the analytical interference of conventional reducible energetic compounds. Detailed evaluations were made for the electrochemical behaviour of NTO on the modified electrode by adsorptive stripping voltammetry, electrochemical impedance spectroscopy (EIS) and chronoamperometry techniques in the pH range of 2.0–10.0. Parameters such as diffusion coefficient constant of NTO were calculated, and various experimental conditions were also optimised. Under optimal conditions the calibration curve had two linear dynamic ranges of 130.0–3251.5 μg L −1 and 6.5–26.0 mg L −1 with a detection limit of 26.0 μg L −1 (0.2 μmol L −1 ) and precision of <3%. This electrochemical sensor was further applied to determine NTO in real soil and water samples with satisfactory results.